A case study of the MAC (masked acyl cyanide) oxyhomologation of N, N-dibenzyl-l-phenylalaninal with anti diastereoselectivity: preparation of (2S, 3S)-allophenylnorstatin esters. Issue 8 (15th February 2022) - He, Xuefeng; Buchotte, Marie; Guillot, Régis; Deloisy, Sandrine; Aitken, David J.
Abstract : The three-component reaction proceeds with unhindered alcohols in good yield and high anti diastereoselectivity to give protected ester derivatives of (2 S, 3 S )-allophenylnorstatin and provides an expedient access to the amino acid itself. Abstract : The three-component reaction between a protected α-amino aldehyde, an alcohol and an α-silyloxymalononitrile provides an expedient access to protected α-hydroxy-β-amino acid derivatives. The prototypical process, performed on N -Cbz-phenylalaninal, is known to proceed with syn diastereoselectivity. The present study demonstrates that the diastereoselectivity of the reaction can be inverted, using the rationale of a Felkin-Anh interaction model. Reactions performed on N, N -dibenzyl-l -phenylalaninal proceed with a high anti diastereoselectivity, providing a panel of synthetically useful ester derivatives of (2 S, 3 S )-allophenylnorstatin. The procedure is exploited to accomplish one of the most efficient syntheses of the title compound to date, in 3 steps (66% yield) from N, N -dibenzyl-l -phenylalaninal.